Recensioni - Ius, Marco; Serbati, Sara (STUDIUM EDUCATIONIS - Rivista semestrale per le professioni educative, 2014)
- Hart A.,Blimcow D., Thomas H., Resilient Therapy. Working with Children and Families, Est Sussex, Routledge, 2007, pp. 216 di Marco Ius; - Ungar M., Counseling in challenging contexts: Working with individuals and families across clinical and community settings, Belmont (CA), Brooks/Cole, 2011, pp. 342 di Marco Ius; - Milani P., Pegoraro E., L'intervista nei contesti socio-educativi: una guida pratica, Roma, Carocci, 2011, pp. 110 di Sara Serbati.